STUDENTS’ MOTIVATION ON VIRTUAL LEARNING OF ENGLISH LANGUAGE AND LITERATURE (ELL) COURSE DURING COVID-19 PANDEMIC - Eka Rosita; Rafi'ah Nur; Siti Hajar Larekeng (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
Students found virtual lessons to be highly frustrating, therefore motivation to study is critical in completing the learning process, particularly in English language and literature courses. The researcher explores how the pandemic covid-19 influences student motivation during the pandemic covid-19 in this thesis. The mix method was utilized in this investigation, along with a sequential explanatory design. Students in class XII from SMAN 7 Wajo who had been attending English language and literature classes both offline and virtual were used as data sources. Respondents come from a variety of social classes. Researchers employed surveys, interviews, and documentation as data sources in this study, with data analysis through Quan-qual that followed Croswell's explanatory design. The data from the questionnaire was examined using quantitative data, while the data from the interview was studied using qualitative data. The researcher would then evaluate the entire data to answer the query difficulties after collecting the analysis.The results showed that students’ motivation was influenced by the covid-19 pandemic situation that used virtual classes for the ELL course. It showed from the data result that showed some motives that influenced the students such as internet connection, willingness to learn, etc.Due to an abundance of free time, some students get lazy and find it difficult to divide their time. Leisure time becomes both a hindrance and a boon. Leisure time provides several opportunities to learn more from various sources, but it also poses multiple challenges, such as a desire not to study. Too many assignments from other courses could stress the students out